2021
DOI: 10.1111/jcmm.17133
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two multi‐focal therapies for glioblastoma: An antibody targeting ELTD1 and nitrone‐based OKN‐007

Abstract: Glioblastoma (GBM) is the most common primary malignant brain tumour in adults. Despite a multimodal treatment response, survival for GBM patients remains between 12 and 15 months. Anti‐ELTD1 antibody therapy is effective in decreasing tumour volumes and increasing animal survival in an orthotopic GBM xenograft. OKN‐007 is a promising chemotherapeutic agent that is effective in various GBM animal models and is currently in two clinical trials. In this study, we sought to compare anti‐ELTD1 and OKN‐007 therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Early studies found that in more than 20 TRP channels, compared with normal brain tissue, TRPM8 mRNA expression in GBM was upregulated to the highest level, which was closely related to the migration, invasion, and proliferation of glioma. 143 TRPM8 suppression or knockdown has been shown to disrupt the trigger of apoptotic cell death, cell cycle, cloning survival, and impair DNA repair. 144 TRPM8 channels may also regulate cell proliferation by dynamically controlling the level of glioma resting potential, which may be a crucial cell cycle regulator.…”
Section: Pathological Functions Of the Trpm Channels In Gliomamentioning
confidence: 99%
“…Early studies found that in more than 20 TRP channels, compared with normal brain tissue, TRPM8 mRNA expression in GBM was upregulated to the highest level, which was closely related to the migration, invasion, and proliferation of glioma. 143 TRPM8 suppression or knockdown has been shown to disrupt the trigger of apoptotic cell death, cell cycle, cloning survival, and impair DNA repair. 144 TRPM8 channels may also regulate cell proliferation by dynamically controlling the level of glioma resting potential, which may be a crucial cell cycle regulator.…”
Section: Pathological Functions Of the Trpm Channels In Gliomamentioning
confidence: 99%
“…During tumor promotion, activated TGF- β led to decreased apoptosis and increased cell proliferation, cell migration, and angiogenesis [ 45 ]. OKN-007 is thought to act via LTBP and downregulates several genes associated with the ECM [ 6 ], and is also a free radical scavenger [ 4 ], resulting in the reversal of the major tumorigenic characteristics, i.e., increases tumor cell apoptosis and decreases cell proliferation, migration and vascular angiogenesis [ 46 ]. Other proteins decreased by OKN-007 include ABCA2, ATP5B, CNTN2, KMT2D, and MYCBP2.…”
Section: Figurementioning
confidence: 99%
“…In Figure 1, we present some examples of nitrones currently being developed as drug candidates for ischemic stroke or other diseases. NXY-059 has been reported to work as a chemotherapeutic agent against glioblastoma [31,32], with several clinical trials being conducted. TBN (tetramethylpyrazine nitrone), derived from 2,3,5,6-tetramethylpyrazine, an active component of the traditional Chinese herb Ligusticum wallichii, combines a thrombolytic effect with potent radical scavenger properties [33] and a good permeability profile, proving to be neuroprotective in ischemic stroke [34], Alzheimer's disease [35] and amyotrophic lateral sclerosis [36] experimental models.…”
Section: Introductionmentioning
confidence: 99%